1
$\begingroup$

I'm trying to work out the following indefinite integral: $\int x^3 \sqrt{1-x^2}$. To solve this, I said let $u=1-x^2$. Then, $\frac{du}{dx}=-2x$, and $du=-2x \cdot dx$, and $dx=\frac{du}{-2x}$. Clearly, $x^3=-((1-x^2)-1)x=-(u-1)x$. I figure that this makes the integral: $\int (-u+1)x\sqrt{u}\cdot \frac{du}{-2x}=\int -\frac{(-u+1)\sqrt{u}}{2}\cdot du$

And I can solve it from there. Is that simplification process correct? I'm concerned that I can't have $x$ values when I'm integrating in terms of $u$, but they cancel out. Does that make it ok to include them?

Thanks for your time.

$\endgroup$
  • 2
    $\begingroup$ As long as the x's canceled you're good $\endgroup$ – randomgirl May 15 '18 at 0:58
0
$\begingroup$

$$\int x^3\sqrt{1-x^2}$$

Apply u-substitution: $u=1-x^2$

$$=\int -\frac{(-u+1)\sqrt{u}}{2}du$$

$$=-\frac12\int(-u+1)\sqrt{u} du$$

$$=-\frac12\int -u^\frac{3}{2}+\sqrt{u}du$$

Apply the Sum Rule,

$$=-\frac12(-\int u^\frac32du+\int \sqrt{u}du)$$

$$=-\frac12(-\frac25u^\frac52+\frac23u^\frac32)$$

Substituting back $u=1-x^2$

$$=-\frac12(-\frac25(1-x^2)^\frac52+\frac23(1-x^2)^\frac32)$$

After doing small calculations,

$$\int x^3\sqrt{1-x^2}=-\frac12(-\frac25(1-x^2)^\frac52+\frac23(1-x^2)^\frac32)+C$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.